O trabalho do psicólogo com as equipes de atendimento a emergências à luz da Justiça Restaurativa - Bittencourt, Sara Cianelli dos Anjos (2019)
This thesis arose due to concerns about the professional practice in emergency and disaster situations, in which is possible to see the emotional distress of the professionals that rescue people in response to emergencies on a daily basis. It appears that these professionals need psychological support after emergency services, since they are often affected by the victims’ initial emotional distress after witnessing it. Therefore, it is necessary an initiative to increase their emotional strength. Using resources from the psychological science to reduce their suffering, this research aims to verify and analyze if the Restorative Justice’s Peace Circle is able to create a place for decompressing and sharing traumatic experiences and to become a social support for these professionals; create an action plan in the period between the pre and post-Circle and with the participants, which may or may not continue autonomously. The methodological procedure used was a quantitative and qualitative research-action, and all the data was gathered through a structured questionnaire sent via Internet to professionals of the state of São Paulo’s Fire Department, Urgent and Emergency Services and Rescue and Emergency Care Group; the practical intervention in the Peace Circle was performed at the Fire Department. The technique used for the data analysis and interpretation was the Thematic Content Analysis technique, using Laurence Bardin’s (1977) contributions as a theoretical background. At the end of this paper, it was concluded that the space provided by the Peace Circle sessions, based on the systematic interpretations, brought decompression and the sharing of experiences. Therefore, it can be passed on as a psychological resource of social support for these professionals